The Role Of Work Environment, Career Development, And Work Life Balance In Post-Pandemi Gen Z Organizational Commitment (Special Study At Pt. Sinar Utama Jaya Abadi) - Nadiah Islamiyah; Achmad Tarmizi (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2023)
Organizational commitment is one of the attitudes in work, which is defined as a person's orientation towards the organization in terms of loyalty, identification, and involvement, Gen Z is known as the job hopper generation because Gen Z prefers to change jobs rather than work with things they don't like. This behavior is certainly related to the concept of organizational commitment. Therefore this study aims to examine and prove the role of the work environment, career development and work life balance in increasing Gen Z organizational commitment after the Covid-19 pandemic at PT. Sinar Utama Jaya Abadi. The methodology used in this study is a quantitative method by distributing online questionnaires consisting of 83 Gen Z employees at PT. Sinar Utama Jaya Abadi. The research data was processed using SPSS analysis.